Freedom of the Press Regulations in Indonesia and Sweden: Limited but Free - Haresti Asysy Amrihani; Rajab Ritonga (Ikatan Sarjana Komunikasi Indonesia, 2021)
Freedom of the press regulations are adhered to by various countries, including Indonesia and Sweden. Every nation wants their country to be free, and uphold freedom of expression and human rights. Sweden is the first country to regulate freedom of expression by enacting Freedom of the Press Act in 1766, while Indonesia has so far implemented Law No. 40 of 1999 on the Press. This article highlights how freedom of the press is implemented in Indonesia so that its index of democracy and freedom of the press is equal to that of Sweden.Â This research applies a literature study method and uses secondary data from various books, journals and legislations. The researcher concludes that some groups encourage the revision of Law No. 40 of 1999 with certain conditions, while others are opposed to it. The other groups stated that the law is lex specialis derogate legi geneari and is used in case of press dispute so that journalists can no longer be imprisoned due to their profession.